The interplay of ADHD characteristics and executive functioning with the GPA and divergent thinking of engineering students: A conceptual replication and extension - Taylor, Christa L.; Zaghi, Arash Esmaili (Frontiers in Psychology, 2022)
Characteristics of attention-deficit hyperactivity disorder (ADHD) and executive functioning difficulties have been found to correspond with poorer academic outcomes on the one hand and enhanced divergent thinking on the other hand. The current study was conducted to better understand the relationship between ADHD characteristics, executive functioning difficulties, divergent thinking, and academic outcomes by conceptually replicating and expanding on a previous study. Undergraduate engineering students (N = 199) at a public university in the northeastern United States completed self-report measures of ADHD characteristics and daily executive functioning, as well as divergent thinking (figural and verbal) and intelligence quotient (IQ) tests. The results of a series of multiple regression models showed that (1) executive functioning difficulties negatively, and non-verbal IQ and figural divergent thinking positively, predicted engineering grade point average (GPA; obtained from the university registrar’s office), (2) GPA and verbal IQ positively predicted figural divergent thinking scores, and (3) verbal IQ positively predicted verbal divergent thinking scores. A series of multiple regression models testing the assertion that controlling for IQ would strengthen the relationship between divergent thinking and ADHD characteristics or executive functioning were not supported but did show associations between select components of characteristics and divergent thinking. Taken together, these results support previous conclusions that students with ADHD characteristics and executive functioning difficulties may struggle academically yet exhibit select enhanced divergent thinking abilities.